基于UG二次开发的2K-H行星齿轮传动虚拟装配 - 韩翔 (Jixie chuandong)
Two kinds of method to implement virtual assembly of 2K-H planet gear transmission-are presented according to UG connection constraint method and dimension-driving. It is pointed out that assembly modeling based on dimension -driving is realized easily by program. In the end, using UG/Open API by making use of dimension-driving technique on the basis of UG/assembly modeling, virtual assembly of 2K-H planetaray gear transmission is implemented. Some code is given out. Practice demonstrators that this assembly modeling can be used for simulation of mechanism animation.